Atuação do escolar trazendo conhecimento para sua própria família: estatística em prevenção de câncer bucal - Homse, Lucas Correa [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The statute of the child and adolescent ensues them effective implementation of the rights to health and encompasses (abrange) the necessity of participation in decision of their interest and respect to their autonomy. Aim: This research ains to verify whether the schoolchildren are capable of raising the awareness of their families conceining some knowledge of health and statistics. The sample was non-probabilistc and intentional with sixth graders of a public school from Araçatuba, SP and their parents. A questionnaire was answered by the schoolchildren and their parents. Lectures on some nations of health focusing mouth cancer and basic nations of statistics were carried out. The schoolchildren were provided with education materials so that they could use them in order to transmit their parents the acquired knowledge. The schoolchildren and their parents were assessed again by applying the same questionnaire. The result showed that there was improvement in the number of the schoolchildren's right answers in 61,1% of the questions, as for the families, 39% of the questions showed wore right answers, therefore, the improvement was lower. The schoolchild/family interrelation could have brought forth better results, however, we believe the aim proposed in this research can be reached as long as the schoolchildren are provided with longer preparation to diffuse knowledge and information awong then families

O Estatuto da Criança e do Adolescente refere-se à saúde da criança e do adolescente como sujeito de direitos e implica na necessidade da participação nas decisões de seu interesse e no respeito à sua autonomia. Objetivo: Verificar se os escolares podem ser capacitados para levar noções de saúde e conhecimentos de estatística aos seus familiares. A amostra (n=86), não probabilística e intencional, foi composta de escolares de 6ª série de uma escola pública de Araçatuba-SP, e seus respectivos pais. Foi aplicado um questionário aos escolares e pais. Foram realizadas palestras na escola sobre noções de saúde com ênfase em câncer bucal e noções básicas de estatística. Foram distribuídos materiais educativos para os escolares utilizarem na transmissão dos conhecimentos adquiridos. Foi realizada nova avaliação, nos escolares e familiares, utilizando o mesmo questionário. Os resultados mostraram que em 61,1% das questões houve melhora no acerto dos escolares. Em relação aos familiares o aproveitamento foi menor, 39% das questões tiveram mais respostas corretas. A inter-relação escolar/família poderia ter sido maior, mas acreditamos na possibilidade de alcançar o objetivo proposto nesta pesquisa, se prolongar o tempo de preparação do escolar para ser o difusor de conhecimento dentro de sua família
Keywords: Neoplasias bucais; Saude; Criança; Saúde bucal; Mouth neoplasms